The effect of foreign-owned large plant closures on nearby firms - Márta Bisztray (Hungarian Academy of Sciences, Institute of Economics, 2016)
I estimate the impact of foreign-owned large plant closures on local firms. I identify 41 such events in Hungary and assign comparable control cities with foreign-owned large plants operating in the same industry and not closing. I use a firm-level panel database of Hungarian firms between 1992 and 2012. I do a difference-in-differences estimation comparing outcomes of firms in the treated and control areas, before and after the plant closure. I find that after the foreign-owned large plant closures sales of nearby firms decreased by 6 percentage points and employment decreased by 3 percentage points on average. Firms operating in local services were hurt even more, suggesting that reduced local purchasing power due to the layoffs is a significant channel of the local plant closure effect. Firms operating in the supplier industry of the closing plant also decreased employment more than average, suggesting that input-output linkages play an important role in the propagation of negative shocks. In contrast, firms in the industry of the closing plant increased their employment, suggesting that they could benefit from the increased local labor supply. I also find that low-productivity firms were hurt more by the plant closures than high-productivity firms.
Keywords: F23; R12; R23; R58; 330; plant closure; agglomeration; local labor market; demand effect; input-output links; propagation of shocks; FDI